Implementasi Managemen Kelas Dalam Keterampilan Membimbing Dan Memudahkan Belajar Oleh Mahasiswa STIPAK - Zain, Diana Meita (DIDAKTIKOS: Jurnal Pendidikan Agama Kristen, 2023)
Classroom management is an effort made by the teacher to streamline learning in class. Classroom management skills are divided into four parts, namely skills in holding a personal approach, organizing skills, guiding skills and facilitating learning, and skills in designing and implementing learning activities. In this study focused on research on guiding skills and facilitating learning.The purpose of this study was to find out how STIPAK students carry out guiding skills and facilitate learning. This study uses a type of qualitative research with a phenomenological approach. The research object was 6 STIPAK Class 2019 students.The results of the study can be concluded that in general, the 6 informants have been able to carry out guiding skills and facilitate learning in three ways, namely giving reinforcement verbally, non-verbally and conducting supervision. However, as PAK teachers, the informants did not provide verbal and nonverbal reinforcement which is characterized by Christianity. In contrast, informants in verbal reinforcement tend to use general verbal expressions such as Good job and high five.